Axial compressive behavior of steel-tube-confined concrete-filled-steel-tubes. (December 2022) - Li, Xiaozhong; Zhang, Sumei; Lu, Wei; Li, Jian
Abstract: Concrete-filled steel tubes (CFST) are widely used in civil engineering practice, and a significant shortcoming of such members is the insufficient and delayed concrete confinement by the steel tube. The configuration of steel-tube-confined CFST (T-CFST), employing an outer steel tube as additional external confinement to the internal CFST, was recently proposed by the authors. The preliminary study has validated the great potential of T-CFST in new construction and strengthening. Against this background, this paper aims to investigate the influence of critical parameters in the axial compressive behavior of T-CFST stub columns through a rigorous systematic experimental study. Test results showed that not only the shear failure was prevented, but also the compressive strength was significantly improved for T-CFST due to the effective concrete confinement by the outer steel tube. Apart from the increasing steel ratio of the outer tube and the inner tube, the concrete confinement also can be enhanced as the ratio of the outer tube and the inner tube steel ratio increases. To fully develop the mechanical properties of T-CFST, sufficient confinement should be employed at the column ends to prevent premature failure there. The development of the longitudinal stress and hoop stress were analyzed and compared for the outer tube and the inner tube, and the calculating method was proposed to determine the longitudinal and hoop stress components at the column compressive strength. Based on the superposition method, a suitable prediction method was proposed to determine the compressive strength of T-CFST, and the prediction results were well close to the experimental results in this study. Highlights: The new column of steel-tube-confined concrete-filled-steel-tubes​ (T-CFST) is tested under axial compression. The influence of key parameters and configurations on the mechanical properties is illustrated. The confinement mechanism T-CFST of different parameters is determined and compared. A suitable prediction method is proposed to determine the compressive strength.